GhVTC1, the Key Gene for Ascorbate Biosynthesis in Gossypium hirsutum, Involves in Cell Elongation under Control of Ethylene - Song, Wangyang (Cells, 2019)
L-Ascorbate (Asc) plays important roles in cell growth and plant development, and its de novo biosynthesis was catalyzed by the first rate-limiting enzyme VTC1. However, the function and regulatory mechanism of VTC1 involved in cell development is obscure in Gossypium hirsutum. Herein, the Asc content and AsA/DHA ratio were accumulated and closely linked with fiber development. The GhVTC1 encoded a typical VTC1 protein with functional conserved domains and expressed preferentially during fiber fast elongation stages. Functional complementary analysis of GhVTC1 in the loss-of-function Arabidopsis vtc1-1 mutants indicated that GhVTC1 is genetically functional to rescue the defects of mutants to normal or wild type (WT). The significant shortened primary root in vtc1-1 mutants was promoted to the regular length of WT by the ectopic expression of GhVTC1 in the mutants. Additionally, GhVTC1 expression was induced by ethylene precursor 1-aminocyclopropane-1-carboxylic acid (ACC), and the GhVTC1 promoter showed high activity and included two ethylene-responsive elements (ERE). Moreover, the 5′-truncted promoters containing the ERE exhibited increased activity by ACC treatment. Our results firstly report the cotton GhVTC1 function in promoting cell elongation at the cellular level, and serve as a foundation for further understanding the regulatory mechanism of Asc-mediated cell growth via the ethylene signaling pathway.